Functional Foods: Exploring the Health Benefits of Bioactive Compounds from Plant and Animal Sources - Versha Dixit; S. William Joseph Kamal; Pranjali Bajrang Chole; Deen Dayal; Kundan Kumar Chaubey; Anish Kumar Pal; Jobi Xavier; B. T. Manjunath; Rakesh Kumar Bachheti (Journal of Food Quality)
“Let food be the medicine” (Hippocrates) is a historic quote that became the basis of food science and nutraceuticals. Due to their possible therapeutic advantages, extracts from food have attracted much interest in the medical community. These extracts are abundant in bioactive compounds, which are natural molecules that may be found in various foods and have been demonstrated to affect health positively. Food components have lots of bioactive components, including primary and secondary metabolites and nutritional components, for example, carbohydrates, proteins, vitamins, minerals, fatty acids, antioxidants, phenolics, and flavonoids. This study’s primary focus is on the make-up and purpose of these bioactive components found in food extracts. This review aims to give readers a thorough grasp of the bioactive substances found in food extracts and their possible physiological uses. These bioactive substances’ functional traits, such as their antioxidant, anti-inflammatory, antibacterial, anticancer, and neuroprotective actions, are also studied. Further research is required to create new functional foods, nutraceuticals, and dietary supplements with specific health advantages that can benefit from understanding these molecules’ structure and function.